Immune Response Generated With the Administration of Autologous Dendritic Cells Pulsed With an Allogenic Tumoral Cell-Lines Lysate in Patients With Newly Diagnosed Diffuse Intrinsic Pontine Glioma - Benitez-Ribas, Daniel; Cabezón, Raquel; Flórez-Grau, Georgina; Molero, Mari Carmen; Puerta, Patricia; Guillen, Antonio; González-Navarro, E. Azucena; Paco, Sonia; Carcaboso, Angel M.; Santa-Maria Lopez, Vicente; Cruz, Ofelia; de Torres, Carmen; et al. (Frontiers in Oncology, 2018)
Background and objective Diffuse intrinsic pontine glioma (DIPG) is a lethal brainstem tumor in children. Dendritic cells (DCs) have T-cell stimulatory capacity and, therefore, potential antitumor activity for disease control. DCs vaccines have been shown to reactivate tumor-specific T cells in both clinical and pre-clinical settings. We designed a phase Ib immunotherapy (IT) clinical trial with the use of autologous dendritic cells (ADCs) pulsed with an allogeneic tumors cell-lines lysate (ATCL) in patients with newly diagnosed DIPG after irradiation (RT). Methods Nine patients with newly diagnosed DIPG met enrollment criteria. Autologous dendritic cell vaccines (ADCV) were prepared from monocytes obtained by leukapheresis. Five ADCV doses were administered intradermally during induction phase. In the absence of tumor progression, patients received 3 boosts of tumor lysate every three months during the maintenance phase. Results Vaccine fabrication was feasible in all patients included in the study. Non-specific KLH (9/9 patients) and specific (8/9 patients) antitumor response was identified by immunologic studies in peripheral blood mononuclear cells (PBMC). Immunological responses were also confirmed in the T lymphocytes isolated from the cerebrospinal fluid (CSF) of 2 patients. Vaccine administration resulted safe in all patients treated with this schema. Conclusions These preliminary results demonstrate that ADCV preparation is feasible, safe and generate a DIPG-specific immune response detected in PBMC and CSF. This strategy shows a promising backbone for future schemas of combination immunotherapy.